Development Of Waste Quantification Models For Malaysian Housing Construction Project Case Study For Brick And Tile Wastes - Hassan, Siti Hafizan (2018)
One of the main contributors to the waste generated in the Malaysian construction industry is housing projects. The construction waste has increased over years, creating environmental problems and profit loss to contractors. Limited data are available to date in Malaysia, especially in terms of sources, types and quantity. Predicting of the waste management via specific model has not been well established. The aim of this study are to explore the causes and contributory factors that cause waste generation in selected housing project followed by development of appropriate waste quantification models for the brick and tile waste, being the most waste materials normally disposed at housing project. Then, waste minimization framework is proposed which may be useable for similar project elsewhere. Site observation and interviews with labours and site management was conducted in determining the waste sources, waste management practices and labours productivity such as age, experience and nationality. The linear regression model was used for the model development. Construction waste in form of concrete, wood, steel, brick, tile, roof trusses, and roof tiles, were investigated individually by weighing and volume measurement methods. The research revealed that wastes generated in Malaysian construction are mainly caused by labours and management problems. The study found that each material has its own contributory factor. The productivity of the labours also related to the age, experience and nationality. The increased of productivity reduced the waste generated in the construction at Site Taman Ilmu, Seri Akasia and Seri Putera. Two prediction models have been developed BW=-2.359+1.605A dan MW=3.361+0.544A (BW= Brick Waste, MW= Tile Waste, A= Area). From the results the accuracy for of the model in predicting the amount of brick waste generated at Site Taman Ilmu is 77.3%, followed by Site Seri Akasia 74.6% and Site Seri Putera 61.6%. For the tile waste, the independent variables explain 91.3% for Site Taman Ilmu, 84.7% for Site Seri Akasia and 72% for Site Seri Putera. Based on performance of the models, the linear regression is found more suitable for the tile waste prediction. For the early estimation, the generated model can predict the amount of brick and tile waste based on the work area from the construction drawing. This will help the site management to take proper action to minimise the amount of brick and tile waste generated.